Innovative leadership and problem solving styles among Malaysian secondary school leaders - Abd Rahman, Hamidon; Othman, Azam; Nordin, Mohamad Sahari; Sheikh Ahmad, Ismail (2015)
Innovative leadership has been prescribed to school administrators as a panacea for the success of their schools. Nevertheless, educational leaders often misconstrue the differences between being innovative and being creative. Principals are sometimes unsure on the differences between the two dimensions. In addition, principals are uncertain on how to be innovative and are static in their comfort zones. This study will try to investigate characteristics of innovative leaders and create an instrument to measure innovative behaviours. The methodology utilised was quantitative method using factor analysis in particular Exploratory (Principal Component Analysis) and Confirmatory Factor Analysis (Structural Equation Modelling). Items in the instruments were clustered into three distinct groups: Personal traits, Organisational factors and Change management. A randomized sample of 218 school principals were chosen as respondents to test the multi dimensions hypotheses and fit-with-item. Analysis using AMOS version 16 shows that it is a multi-dimension construct. Validity was proven with discriminant validity showing acceptable loadings. Keywords: Innovative Leadership, Creativity and Innovative, Problem-solving styles.